Unconventional Fiscal Policy at the Zero Bound - Correia, Isabel; Farhi, Emmanuel; Nicolini, Juan Pablo; Teles, Pedro (American Economic Review, 2013)
When the zero lower bound on nominal interest rates binds, monetary policy cannot provide appropriate stimulus. We show that, in the standard New Keynesian model, tax policy can deliver such stimulus at no cost and in a time-consistent manner. There is no need to use inefficient policies such as wasteful public spending or future commitments to low interest rates. (JEL E12, E43, E52, E62, H20)